2020
DOI: 10.1177/0022022120925907
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Relationship Between Culture and Resilience Capacity in Trauma Survivors

Abstract: Resilience capacity has been found to be associated with individuals’ flexibility and adaptability when dealing with adversity-related stress. Previous research suggested that resilience capacity may play an important role in moderating the relationships between exposure to traumatic events and severity of post-traumatic stress disorder (PTSD) symptoms and cultural factors may be associated with that process. However, adequate research of the mechanisms on how culture may relate to the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…These differences may be explained by the busy working environments in the health-care settings in Hong Kong and the values and beliefs of Chinese people. In a study of trauma survivors, a lower level of dialectical thinking to reconcile opposing perspectives and higher independent self-construal in American trauma survivors affected the effectiveness of their responses in the aftermath of trauma and their construction of a more resilient self-concept than survivors in Hong Kong and China [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be explained by the busy working environments in the health-care settings in Hong Kong and the values and beliefs of Chinese people. In a study of trauma survivors, a lower level of dialectical thinking to reconcile opposing perspectives and higher independent self-construal in American trauma survivors affected the effectiveness of their responses in the aftermath of trauma and their construction of a more resilient self-concept than survivors in Hong Kong and China [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“… Yang and Zhou (2017) also pointed out that individual emotion is not fundamental to well-being in Chinese people. Empirically, while there was no difference between American and Chinese young adults on resilience capability ( Zheng et al, 2020 ), Church et al (2012) showed that Asian colleague students’ autonomy and self-acceptance were significantly lower than their counterparts in the United States. Liu et al (2016) also reported that Chinese adolescents showed higher modesty, self-regulation, prudence than curiosity and humor ( Liu et al, 2016 ), whereas Western adolescents scored higher on integrity, kindness, gratitude but lower on modesty and self-regulation ( Park and Peterson, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study including Shanghai and Hong Kong residents and Americans showed the cultural differences in dialectical thinking, self-construal, and familyism in mediating resilience capacity. Dialectical thinking is the cognitive tendency toward attempts to reconcile two opposing perspectives or acceptance of contradiction [ 108 ]. Self-construal can be the independent self-construal common in the West or the interdependent self-construal common in East Asian countries.…”
Section: Factors Moderating the Impact Of The Stressormentioning
confidence: 99%
“…Similarly, tendency towards familyism (which means interests and gains are conceived at the level of the familial group rather than at the individual level) is present more in East Asian countries [ 94 ]. The study on three regions showed that independent self-construal, familyism, and dialectical thinking significantly mediated the relationship between culture and resilience capacity [ 108 ].…”
Section: Factors Moderating the Impact Of The Stressormentioning
confidence: 99%